PM-IRRAS Assessment of the Compression-Mediated Orientation of the Nanocavity of a Monoacylated β-Cyclodextrin in Monolayers at the Air−Water Interface - Vico, Raquel Viviana (2010)
The structural orientation adopted along the compression-decompression isotherm by a monoacylated beta-cyclodextrin (C16-betaCD) at the air-water interface was assessed by polarization-modulation infrared reflection-adsorption spectroscopy (PM-IRRAS). The adoption of different orientations of the cyclic oligosaccharide unit, relative to the interfacial plane, was interpreted analyzing the PM-IRRAS band intensity ratios of specific vibrations corresponding to the cyclodextrin moiety as a function of the surface pressure for successive compression/decompression cycles. The spectroscopic analysis revealed that the cyclic oligosaccharide modifies its position under compression from one in which the plane of the cavity of the monoacylated beta-cyclodextrin lies almost parallel to the interface to another in which the plane of the cavity is perpendicular to the interface. Through the PM-IRRAS analysis, it was also possible to evidence the establishment of an intermolecular hydrogen bonding network that may play an important role in the dynamic properties of the monolayer packing. The hydrogen bonding network becomes more important with the increases of surface pressure, up to a molecular packing limit, and it imparts the surface properties of the film for future compression-decompression cycles.